Construção de um indicador qualitativo (status de saúde) para avaliação da qualidade de saúde animal de propriedades rurais - Padovani, Carlos Roberto [UNESP]; Stachissini, Anne Valeria Mendonça [UNESP]; Costa, Heni Falcão da [UNESP]; Aragon, FlÁvio Ferrari; Modolo, Jose Rafael [UNESP] (My University, 2011)
Aiming at developing a tool for assessing the magnitude of farm animal health, an indicator named herd “animal health status” was built. To illustrate the construction of the indicator, serum samples were taken from 923 goats on 17 goat farms in the state of Sao Paulo, Brazil, where three diseases were evaluated along with their impact percentages: caprine arthritis encephalitis, toxoplasmosis and neosporose – all of an infectious and transmissible nature and the cause of considerable economic losses. The mathematical rationale underlying the building of the “animal health status” indicator ranks properties on a 0 - 100% scale in terms of disease positivity in the herd, with the lowest indicator value indicating the highest cumulative disease frequency (0% = all animals tested positive for the three diseases, 100% = all animals tested negative for all diseases). Anti-T. gondii, anti-N. caninum and anti-CAEV antibodies were tested using indirect immunofluorescence reaction (IIFR ≥ 16), Neospora agglutination test (NAT ≥ 25) and agarose gel immunodiffusion (AGID positive or negative), respectively. The animal health status of the farms ranged from 32.38% to 96.40% according to disease positivity. The animal health status value will have a direct reflection on the production chain both on and off the farm, providing not only great market advantages, due to how the expression of animal health will add value to livestock farms, as well as on the consumer who can check the quality of animal health at the beginning of the production chain.

Visando à construção de uma ferramenta de trabalho que permitisse expressar a grandeza da saúde animal de propriedades rurais, foi construído um indicador resultante da qualidade da saúde do rebanho denominado “status de saúde animal”. Como exemplo para a construção do indicador, tomaram-se os soros de 923 caprinos oriundos de 17 capris do Estado de São Paulo, nos quais se avaliaram três enfermidades e seus respectivos impactos percentuais: a artriteencefalite caprina, a neosporose e a toxoplasmose - todas de caráter infeccioso e transmissível e que ocasionam consideráveis perdas econômicas. A lógica da construção matemática do “status de saúde animal” classifica a propriedade numa variação de 0 a 100%, conforme a positividade das enfermidades no rebanho: quanto maior a frequência acumulativa de ocorrência das doenças nos animais, menor o valor do indicador, chegando ao limite de 0% - quando todos os animais estiverem positivos às três enfermidades e de 100% - quando todo o rebanho for negativo. Para detecção de anticorpos anti-T. gondii, anti-N. caninum e anti-CAEV, foram utilizados, respectivamente, reação de imunofluorescência indireta (RIFI ≥ 16), teste de aglutinação para Neospora (NAT ≥ 25) e imunodifusão em gel de agarose (IDGA positivo ou negativo). O “status de saúde animal” das propriedades rurais variou de 32,38% a 96,40%, de acordo com a ocorrência de positividade para as enfermidades. A característica do valor do “status de saúde animal” terá reflexo direto na cadeia de produção dentro e fora da fazenda, proporcionando não somente enormes vantagens mercadológicas, devido à expressão que a saúde animal terá para agregar valor às propriedades rurais de produção animal, mas também no consumidor final que poderá verificar a qualidade da saúde animal no início da cadeia de produção.
Building quantitative (health status) indicators for the assessment of animal health quality on farms
Keywords: Status; Animal health; Toxoplasmosis; Neosporosis; CAE; Status; Saúde animal; Toxoplasmose; Neosporose; CAE